PENGARUH TINGKAT INFLASI, TINGKAT SUKU BUNGA DAN JUMLAH UANG BEREDAR TERHADAP NILAI TUKAR RUPIAH PADA DOLLAR AMERIKA - Putu Diah Putri Idawati (Forum Manajemen, 2015)
The growth of a stable currency value indicates that the country hasa relatively good economic condition or stable. Exchange rate instability affectsinvestment and capital flows or International trafficking. The influence of the rate ofinflation, interest rates, and the money supply to the exchange rate on the US dollarand tested by multiple regression analysis techniques. During the study observationperiod of five years from the year 2009 to 2013. The results of this study demonstratethat the level of interest rates and the money supply effect on the exchange rate inthe US dollar. Meanwhile, the inflation rate showed no effect results. Simultaneously, the rate of inflation, interest rates, and the money supply effect on the exchange rate on the US dollar.